Update and Expansion of the HIV/AIDS Prevention Program Archive (HAPPA) - Josefina J. Card; Shayna D. Cunningham; Emily N. Newman; Rachel E. Golden (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Established in 1996 with funding from CDC and NIH, the HIV/AIDS Prevention Program Archive (HAPPA) is now the biggest private sector collection of HIV-related evidence-based behavioral interventions (EBIs). Each EBI in HAPPA has been determined by a distinguished Scientist Expert Panel to have demonstrated efficacy in preventing HIV or its risk-related behaviors in the United States. The multimedia replications kits contain everything that a new site would need to implement an EBI such as a user guide that gives an overview of the program and the evidence of its effectiveness; a facilitator’s manual that gives step-by-step implementation protocols for each session; and session implementation materials referenced in the facilitator's manual such as slides, video clips, participant handouts, activity masters, checklists, and homework assignments for the next session. The program packages also contain evaluation materials such as surveys and questionnaires that were used in the original demonstration of effectiveness and that may be used to re-evaluate the program as implemented in a new setting. Recently, we have expanded HAPPA’s scope to include HIV EBIs developed globally and to include evidence-based structural interventions (effective in modifying the physical, social, cultural, political, economic, legal, and/or policy aspects of the HIV risk environment). This paper describes HAPPA’s procedures for identifying, selecting, acquiring and packaging HIV EBIs. It also provides comprehensive lists of evidence-based HIV behavioral and structural interventions and gives information on how to access EBI program packages for implementation in new settings.
Keywords: HIV/AIDS